Science Teacher Candidates’ Thoughts About Global Warming Studying in Turkey and United Kingdom - Demet Sever (Elementary Education Online, 2023)
Teachers have important roles in raising awareness of students about global warming and educating them as environmentally conscious individuals. Being a good environmental educator is related with the knowledge of the teachers in the area. The aim of the study is to identify the level of awareness and knowledge about global warming of science teacher candidates’ who are studying in Turkey and United Kingdom. In this qualitative research data was obtained from 14 teacher candidates (7 from Turkey, 7 from United Kingdom) via semi- structured interviews. In data analysis procedure descriptive analysis method was utilized and teacher candidates’ comments were coded thematically. Findings revealed that neither teacher candidates in Turkey nor those in United Kingdom have adequate awareness and knowledge about global warming.